Flujo de genes entre frijol común y silvestre en Costa Rica - Chaves-Barrantes, Néstor Felipe; Araya Villalobos, Rodolfo; Debouck, Daniel G. (2009)
In order to study gene flow between common wild and cultivated cultivated bean, the rate of allogamy was estimated in a location where wild common bean grows naturally and at an experimental station. In 2004, natural outcrossing between wild Mexican bean G23511A (Phaseolus vulgaris L.) and white cultivar PAN68 was estimated at Fabio Baudrit Experimental Station of the University of Costa Rica in Alajuela. Two experimental plots were sown; each one had two blocks of ten rows of PAN68 (15m long and 0,6m spaced). Between blocks and at their upper border, three rows of wild Mexican common bean were sown as pollen donors. Each of the rows and plants in the white blocks was numbered. In 2005 and 2006 in Quircot, Cartago, where wild common bean grows naturally, plants of common bean (Vainica de Palo) were sown in six locations adjacent to wild common bean populations. In both locations, flowering of wild and cultivated bean was coincident. All seeds from assays were harvested and germinated in seedlingtrays, estimating the rate of allogamy through the color of the hipocotyl (purple), which indicates what seedlings were crossed. In Alajuela, natural crossing ranged from 0,007 to 0,028 %, whereas in Quircot from 0 to 0,199 %.